Prevalence and genotypic distribution of hepatitis GB-C/HG and TT viruses in blood donors, mentally retarded children and four groups of patients in Eastern Anatolia, Turkey - Kalkan, A; Ozdarendeli, A; Bulut, Y; Saral, Y; Ozden, M; Kelestimur, N; Toraman, ZA (Natl Inst Infectious Diseases, 2005)
We investigated the prevalence and genotypic distribution of GB virus-C/hepatitis G virus (GBVC/HGV) and TT virus (TTV) in blood donors, mentally retarded children and four groups of patients living in Eastern Anatolia, Turkey. The prevalence and genetic analysis of TTV were determined by using the primers of the UTR and ORF1 regions of TTV, respectively. Reverse transcription nested (RT-n)-PCR was used to amplify 5' UTR of GBV-C/HGV Genotyping of HGV was carried out by PCR-based genotyping assay while RFLP was conducted to determine the genotypes of TTV. TTV DNA was detected in 118 of 4 10 sera tested, giving an overall prevalence of 28.7%; GBV-C/HGV-RNA was detected in only 17 cases, giving an overall prevalence of 4.1%. No significant differences were observed in the number of positive or negative tests for GBV-C/HGV and TTV according to duration of illness or mean duration of institutionalization in any of the groups studied. Although all samples from the study population belonged to genotypes I and 4, the most common TTV genotype is G2. In conclusion, our results indicate a low endemicity of GBV-C/HGV and TTV infection in Eastern Anatolia, Turkey. The presence of G2 strains reveals the limited genetic diversity of the GBV-C/HGV circulating in Turkey. We suggest that TTV infection of genotypes I and 4 is prevalent in the same region.
Keywords: Posttransfusion Hepatitis; Molecular-Cloning; Infection; Primers; Disease; Transmission; Genomes; Region; 4Th; Pcr